Konsep Dan Prinsip Keuangan Sosial Islam - Nasution, Edi Marjan; Marliyah, Marliyah; Siregar, Saparuddin (ITB AAS INDONESIA, 2024)
Islamic Social Finance has an important role in sharia teachings such as zakat alms and waqf. These principles have long been stated in the Koran and al-Hadith. This research discusses the concepts and principles of Islamic Social Finance contained in the texts and those that apply in Indonesia. The research method